Refining Academic Conversations through Discourse with the Imperative Politeness Function - Muhammad Hanafi; Abdul Kadir; Andi Sadapotto; Muhammad Nawir; Suleha Suleha (STAI Hubbulwathan Duri, 2024)
This study aims to describe the function of using politeness as an imperative in academic interaction. The deep data collection study was done through three techniques: recording, observation, and interviews. The in-depth data study analyzed in this research is in the form of recorded data from lecturers' and students' speeches. The selected data is the result of lecturers' speeches to students and students' speeches to lecturers in lectures which contain the imperative function of politeness. Note data fields in the form of recorded data fields descriptive and reflective. In addition, research data can be obtained from generation in a way creative intuition language researcher. The results of the research show that the use of imperative politeness functions by lecturers towards students includes: (1) commanding function, (2) requesting function, (3) prohibiting function, (4) inviting function, (5) suggesting function, (6) expecting function, (7) encouraging function, and (8) urging function. Use function politeness, which is imperative from student to lecturer in academic interaction, includes (1) function application and (2) function request. Politeness markers used to represent the function of imperative politeness in academic interaction include (1) linguistic politeness markers, (2) persona markers, and (3) informal diction markers. The study reveals that lecturers with power in the classroom often consider linguistic politeness in speaking, allowing students to express their speech the way the lecturer speaks. However, this can lead to a lack of harmony between lecturers and students, and may not set an example for students in speaking.